Performance Evaluation of the Dual-Core Based SGI Altix 4700 - Fatoohi, Rod (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2007)
The newest SGI Altix system is the 4000 series that uses dual-core Itanium-2 p9000 series processors. It differs from the Altix 3000 series in the processor architecture and in the type and number of the component modules. Here we compare and contrast between the Altix 4700 and Altix 3700/BX2 using a set of communication benchmarks, kernel benchmarks, and NSF application benchmarks. The communication benchmarks show that the 4700 has a higher effective bandwidth than the 3700/BX2 while the computation benchmarks show the two systems perform at comparable rates except where the application was able to take advantage of a larger L2 cache and faster memory bus on the 4700.